2008
DOI: 10.1302/0301-620x.90b4.20414
|View full text |Cite
|
Sign up to set email alerts
|

Transferring simulated arthroscopic skills to the operating theatre

Abstract: The aim of this study was to investigate the effect of laboratory-based simulator training on the ability of surgical trainees to perform diagnostic arthroscopy of the knee. A total of 20 junior orthopaedic trainees were randomised to receive either a fixed protocol of arthroscopic simulator training on a bench-top knee simulator or no additional training. Motion analysis was used to assess performance objectively. Each trainee then received traditional instruction and demonstrations of diagnostic arthroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
186
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(202 citation statements)
references
References 21 publications
3
186
0
4
Order By: Relevance
“…The incorporation of VR simulators in training regimes offers the potential to reduce error rate which, as well as improving patient outcomes and satisfaction, will also reduce fiscal burden by decreasing the risk of litigation. Seymour et al (2002) showed skills transfer from training on a simulator to the operating theater, and this has been emulated by other studies (Ahlberg et al 2007, Verdaasdonk et al 2008, Larsen et al 2009) including 1 with an orthopedic arthroscopic simulator (Howells et al 2008). Other factors to consider include gender differences, hand dominance, and age correlated with objective scoring.…”
Section: Discussionmentioning
confidence: 86%
“…The incorporation of VR simulators in training regimes offers the potential to reduce error rate which, as well as improving patient outcomes and satisfaction, will also reduce fiscal burden by decreasing the risk of litigation. Seymour et al (2002) showed skills transfer from training on a simulator to the operating theater, and this has been emulated by other studies (Ahlberg et al 2007, Verdaasdonk et al 2008, Larsen et al 2009) including 1 with an orthopedic arthroscopic simulator (Howells et al 2008). Other factors to consider include gender differences, hand dominance, and age correlated with objective scoring.…”
Section: Discussionmentioning
confidence: 86%
“…This raises the question of whether any skill acquired pertaining to these tasks (which are unlikely to be practiced that year) will be retained after the completion of this module. Skills acquired in simulation laboratories need to be practiced to be retained, and without continued practice the skills may be completely lost in due time [5,6]. Emphasis on techniques interns actually perform may, in time, be used to structure the surgical skills curriculum more effectively.…”
Section: Limitations Of the Surgical Skills Curriculummentioning
confidence: 99%
“…While clear goals and objectives for the modules may be developed with relative ease, evidence that surgical simulation skills readily transfer to the operating room is lacking. For example, we do not yet know whether the skills taught during the arthroscopy portion of this curriculum will correlate with performance during an actual procedure [5][6][7].…”
Section: Limitations Of the Surgical Skills Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to perform technical procedures will always be best assessed in the operating room but it can be difficult to standardize surgical procedures [33], manage time restraints [16], and ensure optimal patient safety and clinical outcomes [26]. For these reasons, simulation increasingly is being used to provide opportunities for residents to perform procedures independently, demonstrate knowledge and skills deficits, and commit errors before actually performing surgery on patients in the operating room [2,7,8,13,21,26]. At this time, the best method of assessing a resident's ability to perform an entrustable professional activity independently is unknown.…”
Section: Introductionmentioning
confidence: 99%